PENGARUH LIMBAH DETERGEN INDUSTRI LAUNDRY TERHADAP MORTALITAS, KONSENTRASI HEMOGLOBIN DAN JUMLAH TROMBOSIT IKAN NILA (Oreochromis niloticus) - Saparuddin Saparuddin (Department of Biology Education of Universitas Islam Negeri Alauddin Makassar, 2019)
The aim of this study is to determine the effect of laundry industry residues on the level of toxicity, hemoglobin concentration and platelet count. The waste from the laundry industry is explained in Tilapia's pisciculture facilities. This is a completely randomized design (CRD) with six treatments and three repetitions. The treatments P0 (0%) as control, P1 (1%), P2 (2%), P3 (3%), P4 (4%) and P5 (5%). The observations showed the appearance of tilapia mortality at different treatment concentrations. The highest mortality occurred in the P4 treatment (4%) of 7 animals. In addition, there is also a decrease in hemoglobin concentration. The lowest hemoglobin concentration was found in the P2 treatment of 7.05 gr%. In contrast, the waste from laundry industry did not have a significant effect (P> 0.05) on platelet counts. Based on this study, it indicate that the wastage of the laundry industry affects the survival rate and oxygen supply as seen from the reduced level of tilapia hemoglobin.